PERSEPSI MAHASISWA TERHADAP KUALITAS PELAYANAN PERPUSTAKAAN (SURVAI DI UNIVERSITAS MUHAMMADIYAH METRO) - Nurlaila, Siti (Lembaga Penelitian UM Metro, 2016)
The main objective of this research was to determine how students' perceptions of the quality of library services Muhammadiyah University of Metro. Perception analysis based on five dimensions of service services, namely reliability, responsiveness, assurance, empathy, and tangibles. The samples used in this analysis are as many as 102 people who are students of Muhammadiyah University of Metro by using proportional random sampling. Data were collected by questionnaire. Measurements using a Likert scale. Before collecting data, it must first be tested for validity and reliability. Data analysis using descriptive analysis to see the total Â mean value. Based on the analysis of the data shows that students' perceptions of the quality of library services are very satisfied with the mean total 111.84 with F = 38 out of 101 students. It shows that students have the perception that highly satisfied with library services quality Muhammadiyah University of Metro.